Harnessing silicon nanoparticles and various forms of silicon for enhanced plant growth performance under salinity stress: application and mechanism - Khwaja Salahuddin Siddiqi; Azamal Husen; Noreen Zahra; Abdul Moheman (Discover Nano)
Abstract Agricultural production faces significant losses due to salinity, drought, pests, insects, and weeds, particularly in nutrient- and fertilizer-deficient soils. This review focuses on enhancing the productivity of crops grown in dry and saline environments. Silicon nanoparticles (Si NPs) and silicon compounds (SiO₂/SiO₃2⁻) have shown potential to improve crop yields while mitigating the effects of biotic and abiotic stresses. As an eco-friendly alternative to chemical fertilizers, herbicides, and pesticides, Si NPs stimulate germination, plant growth, biomass accumulation, and nutrient absorption due to their small size, large surface area, and ease of cellular penetration. These nanoparticles reduce salinity stress by modulating gene expression, leading to the activation of antioxidant enzymes such as SOD, CAT, and APX, which help combat reactive oxygen species (ROS). Treatment with low concentrations of nano-silica (100–300 mg/L) significantly enhances plants' tolerance to salinity. Si NPs, when combined with soluble polymeric materials and rhizobacteria, provide a sustainable impact due to their slow-release properties, offering prolonged protection against bacterial and viral infections under saline stress conditions. Graphical abstract